A dynamic active energy demand management system for evaluating the effect of policy scheme on household energy consumption behavior. (November 2015) - Yu, Biying; Tian, Yaming; Zhang, Junyi
Abstract: To reduce the continuously increasing energy consumption in the household sector, including residential and private transport sectors, it is important to design a proper policy scheme to regulate household energy demand. However, determining how to evaluate the collective effect of multiple countermeasures in one policy scheme on household energy related behavior is very challenging; furthermore, the potential interactions between policies due to the timing effect cannot be overlooked. Under these concerns, this study provides a quantitative methodology by developing a DAEDMS (dynamic active energy demand management system) that can evaluate the overall effects of urban planning, soft policies for improving household/individual awareness, technology-improvement/rebate policies, market end-use diffusion control, and social-interaction oriented policies. The timing effect is directly incorporated by allowing the free setting of the execution period for each policy. Building on this demand management system, the quantified policy schemes and the pathways that can reach the target of energy conservation become straightforward, providing helpful support for policy planning. Besides, the variant effectiveness of policy schemes due to different policy timings admonishes the policy makers to realize that the current fragmented regime of policy making between different departments is undesirable for capturing the genuine effect of all of the policies. Highlights: Reducing household energy use needs demand management to regulate household behavior. A dynamic active energy demand management system for household sector is proposed. The collective effect of the policy scheme on household energy use is evaluated. The interaction between policies due to the timing effect is specifically considered. Policies of land use, technology, awareness, market, and social norms are effective.